Mental Health and Physical Activity Among Undergraduate Students in a Quality of Living Course During the COVID-19 Pandemic - Sherrington, Kristen (Université d'Ottawa / University of Ottawa, 2022)
Background & Purpose: University students have lower levels of mental health compared to the general population (Twenge et al., 2019). Since the beginning of the COVID-19 pandemic, a further decline in university student mental health has been reported, emphasizing the growing concern for this population (Chen & Lucock, 2022). Positive education (i.e. courses grounded in positive psychology) could provide undergraduate students with techniques to cope with life, academic, and pandemic stress as growing research has shown its effectiveness in improving well-being (Smith et al., 2021; Yurayat & Seechaliao, 2021). However, to our knowledge, no studies have qualitatively investigated the long-term impact of a semester-long positive education course on university students mental health. Further, no studies have been found that examine the long-term impact of positive education on student mental health during the COVID-19 pandemic. Therefore, the first purpose of the thesis is to explore the perspectives of students who took a Quality of Living course on if and how they believe the course influenced their mental health a) 1-year after taking the course and b) during the ongoing COVID-19 pandemic (RQ1). Additionally, physical activity is a well-researched predictor of mental health and is a first-line treatment for depression (Fortier et al., 2020; Ravindran et al., 2016). There are studies that suggest a bi-directional relationship between physical activity and mental health may exist (Da Silva et al., 2012; Kim et al., 2017). Yet the influence of mental health on physical activity is just emerging. To our knowledge, no studies have used a mixed methods approach to investigate the potential bi-directional relationship between physical activity and mental health in university students and during the COVID-19 pandemic. Thus, a secondary aim of this thesis is to use a mixed-methods approach to explore the bi-directional relationship between physical activity and mental health over time amongst the students who took the QOL course during the ongoing COVID-19 pandemic (RQ2). It was hypothesized that there would be a bi-directional relationship between physical activity and mental health (Kim et al., 2017). Methods: RQ1: The sample consisted of 10 university students who took the course in the Winter 2020 semester. Participants were chosen using purposive sampling from those who indicated interest and were interviewed. Semi-structured interviews were conducted 1-year after the class ended using an interview guide and a pre-interview package was sent prior to the interview. Thematic analysis of the transcripts was performed to generate common themes once data saturation occurred. RQ2: As part of a larger study investigating the Quality of Living course, quantitative data was collected (n=57). Physical activity and mental health were measured before (baseline) and after (endpoint) the course through validated self-report questionnaires and was analyzed using cross-lagged correlational analysis. For the qualitative component, during the semi-structured interviews additional questions were asked to address RQ2. Abductive thematic analysis was used to analyze the transcripts and generate common themes. Results: RQ1: Overall, there were three primary themes identified in the data including The Influence of the Course on Mental Health, Helpful Course Components, and Transferring the Course Topics to One’s Personal Life During the COVID-19 Pandemic. RQ2: The quantitative data were non-significant and did not support the hypothesis. However, the qualitative data supported the presence of a bi-directional relationship and the students agreed that physical activity influences mental health and vice versa. Conclusions: These results suggest that positive education courses like the one investigated in this study could play a valuable role in improving undergraduate students' mental health long-term. These results can be used to inform the development and implementation of future positive psychology courses. Finally, a bi-directional relationship was qualitatively shown to exist and should be further investigated as understanding this relationship can help inform wellness interventions. Future research is recommended on these topics.
Keywords: Mental Health; COVID-19; Physical Activity; Undergraduate Students; Positive Education; Positive Psychology